Quand l’album de jeunesse innove pour mettre en scène la guerre - Nelly Chabrol Gagne (Amnis)
This article proposes an analysis of some images from contemporary children’s picture books, in French or translated into French. Three focal areas will be emphasised to show how wars are staged. On the one hand, autobiographical writing testifies about the childhood of two author illustrators, Uri Shulevitz and Peter Sis, who lived during a time of war, after the bombing of Warsaw or behind the Iron Curtain. On the other hand, writing to the limit, chosen by Pef and Dedieu, insists on the preoccupation of confronting the reader with images depicting the horrors of wars massacring civilians or the hellendured by soldiers during the First World War. Finally, contrapuntal writing considers how artists work in pairs. Davide Cali and Serge Bloch or Didier Lévy and Katrin Stangl exploit the iconotextual potential of the children’s picture book to denounce war whilstendorsing the winning forces of intelligence and imagination at the same time. Hence, when it comes to children’s picture books on twentieth century conflicts, some of the boldness of pictorial and publishing creation will be highlighted.